A New Method for Deriving the Nightside Thermospheric Density Based on GUVI Dayside Limb Observations. Issue 2 (22nd February 2020) - Yu, Tingting; Ren, Zhipeng; Yu, You; Wan, Weixing
Abstract: We propose a new method to derive the nightside thermospheric density by extending Global Ultraviolet Imager (GUVI) dayside limb observations using empirical orthogonal function (EOF) analysis. First, we acquire the GUVI dayside total mass density during 2002–2005 to construct a preliminary empirical model (EM). Simultaneously, we decompose the background thermospheric density from U.S. Naval Research Laboratory Mass Spectrometer and Incoherent Scatter Radar Extended model into different EOFs. The decomposed EOFs are then used to fit the continuous density from EM, to develop a new nightside extended model (NEM). The preliminary EM and developed NEM are further evaluated with Challenging Minisatellite Payload (CHAMP) satellite observations. Higher correlation coefficients and smaller relative standard errors between CHAMP observations and the NEM results are obtained than those between CHAMP observations and the EM results, and the NEM results are in good agreement with the CHAMP observations in time series during both daytime and nighttime, which all prove the NEM method is effective to the reproduction and extension of GUVI original dayside observations. Furthermore, the NEM reveals two typical seasonal variation features, the semiannual variation and equinoctial asymmetry of thermospheric density. The model provides an effective tool to derive the nightside thermospheric density and explore the thermospheric intrinsic structure, and needs the further development to achieve more widespread application of the thermosphere. Key Points: A new nightside extended model (NEM) is established to extend GUVI dayside limb observations using an empirical model (EM) and EOF analysis In contrast with EM, the NEM has better correlation with CHAMP observations, and the NEM and CHAMP results are consistent in time series The NEM provides an effective tool to explore the thermospheric seasonal variations in dayside and nightside